2019
DOI: 10.1038/s41598-019-44671-9
|View full text |Cite
|
Sign up to set email alerts
|

Tendons from kangaroo rats are exceptionally strong and tough

Abstract: Tendons must be able to withstand the forces generated by muscles and not fail. Accordingly, a previous comparative analysis across species has shown that tendon strength ( i . e ., failure stress) increases for larger species. In addition, the elastic modulus increases proportionally to the strength, demonstrating that the two properties co-vary. However, some species may need specially adapted tendons to support high performance motor activities, such as sprintin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…This finding indicates an increase in the role of elastic energy return from downhill walk to uphill gallop and adds to the debate about the role of tendon compliance in small mammal locomotion (Ker et al, 1988;Bullimore and Burn, 2005). The strains we recorded for the rat Achilles tendon in vivo match well with the data from recent materials testing of the same tendon (Javidi et al, 2019). Because MG fascicle strains showed little evidence of net lengthening across all gait-slope conditions, energy stored in the MG tendon during force development is presumably recovered to power limb and body movement, rather than being dissipated by doing work on the muscle (via fascicle stretch; i.e., "elastic backfire"; sensu (Roberts and Azizi, 2011); in contrast to the buffering of rapid stretch and energy absorption observed for turkey landings from drops of different heights and for landings from human jumps (Werkhausen et al, 2017;Werkhausen et al, 2018;Helm et al, 2019;Hollville et al, 2019).…”
Section: Discussionsupporting
confidence: 82%
“…This finding indicates an increase in the role of elastic energy return from downhill walk to uphill gallop and adds to the debate about the role of tendon compliance in small mammal locomotion (Ker et al, 1988;Bullimore and Burn, 2005). The strains we recorded for the rat Achilles tendon in vivo match well with the data from recent materials testing of the same tendon (Javidi et al, 2019). Because MG fascicle strains showed little evidence of net lengthening across all gait-slope conditions, energy stored in the MG tendon during force development is presumably recovered to power limb and body movement, rather than being dissipated by doing work on the muscle (via fascicle stretch; i.e., "elastic backfire"; sensu (Roberts and Azizi, 2011); in contrast to the buffering of rapid stretch and energy absorption observed for turkey landings from drops of different heights and for landings from human jumps (Werkhausen et al, 2017;Werkhausen et al, 2018;Helm et al, 2019;Hollville et al, 2019).…”
Section: Discussionsupporting
confidence: 82%
“…A secondary motivation of the study was to examine the impact of using commonly assumed generic elastic modulus data for mammalian tendon (Ker, 1981;Bennett et al, 1986;Shadwick, 1990;Pollock and Shadwick, 1994b) versus recent species-specific measurements of material properties for kangaroo rat ankle extensor tendons (Javidi et al, 2019a). Based on these new tendon modulus values, our data support the advantageous role of increased tendon compliance for elastic energy recovery, at least in our desert kangaroo rat model.…”
Section: Tendon Materials Propertiessupporting
confidence: 51%
“…However, in 2019, Javidi et al revealed the ankle extensor tendons of desert kangaroo rats (Dipodomys deserti) to be considerably less stiff than originally thought, with elastic moduli values falling close to half the original 1 GPa assumption. In fact, several studies have shown elastic moduli values across other rodent species to be consistently and considerably lower than 1 GPa (Huang et al, 2003;Lavagnino et al, 2005;Legerlotz et al, 2007;LaCroix et al, 2013;Javidi et al, 2019a). Thus, while kangaroo rats do have relatively thicker tendons than larger bipedal hoppers (Biewener et al, 1981;Biewener and Blickhan, 1988), their tendons are considerably more compliant than had been assumed.…”
Section: Journal Of Experimental Biology • Accepted Manuscriptmentioning
confidence: 97%
See 2 more Smart Citations